Influence of long-term stored oil on wettability and its recovery in depleted petroleum reservoirs. (November 2022) - Elsayed, Mahmoud; Al-Abdrabalnabi, Ridha; Zhou, Xianmin; Wu, Yu-Shu
Abstract: Underground oil storage is a viable technique to increase energy security in the context of global concern for oil demand and supply. When the economic conditions permit, it makes sense to store oil in water-flooded, water-wet sandstone reservoirs that are geographically ubiquitous and abundant, structurally safe, and cost-effective for storing large amounts of crude oil safely. Due to long-term restoring oil contacting with the surface of rocks in such reservoirs, the property of the reservoir rocks may be changed, and the performance of oil reproduction may be different. These important factors are related to the change of wetting behavior of reservoirs, which directly affects the recovery rate of stored oil and the relative permeability characteristic of oil and water flow during the reproduction of stored crude oil in a water-wet depleted petroleum reservoir. Unfortunately, there is a lack of study on these research areas. This study investigates the change of wettability in such reservoirs and its influence on the production of stored oil by a second water flooding process. Several experimental techniques, including NMR and centrifuge measurements (USBM), and two-phase flow relative permeability measurement, are employed to investigate wetting behavior in crude oil/water/rock systems and two-phase flow characteristics when the crude oil is reinjected and stored oil is reproduced by water flooding in the present work. Based on the results of NMR and centrifuge experiments, the wettability of the core aged with crude oil was altered from strongly water-wet to weakly water-wet with an increase in aging time. NMR and USBM wettability indexes showed a good agreement suggesting a change into weakly water wetness. It is consistent with the change of relative permeability characteristics for first and second water flooding. We also reported that 77.5% of stored oil is recovered by second water flooding. Oil recovery factors and the characteristic parameters, S w i, K o ( S w i ), S o i, S o r, S w ( m a x ), and K w ( S o r ) were experimentally determined for initial and second water flooding. Although not all of the stored crude oil has been recovered due to wettability change and oil film left the pore's surface on the rock, the desired recovery factor has been achieved during the second water flooding.